Semi‐polar (11‐22) GaN grown on patterned (113) Si substrate. Issue 5 (27th January 2016) - Yu, Xiang; Hou, Yaonan; Shen, Shuoheng; Bai, Jie; Gong, Yipin; Zhang, Yun; Wang, Tao
Abstract: An epitaxial growth technic has been developed to synthesize semi‐polar (11‐22) GaN on (113) Si substrate with inverted‐pyramid patterns. The reaction between Ga and Si substrate has been successfully solved by simply depositing a thin SiO2 layer on selective regions of the substrate before growth. High quality semi‐polar (11‐22) GaN‐on‐Si with a smooth surface has been obtained after delicately tuning growth conditions. Based on the scanning electron microscopy and x‐ray diffraction characterizations, a model has been well established to illuminate the growth process. Due to the very low density of defects confirmed by transmission electron microscopy, our sample demonstrates an excellent optical property, which is promising for efficient optoelectronic devices using GaN‐on‐Si configuration. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)